A Política avaliativa de desempenho dos servidores técnico-administrativos da Universidade Federal da Paraíba e sua repercussão nos serviços de atendimento ao público na instituição - Ferreira, Raquel Pereira de Lima Rodrigues (2019)
Besides legal requirements, the civil servants’ professional performance evaluation stands for a management tool at the administrative sphere that can measure those servants’ performance in their duties, which takes place in all public bodies and entities, either direct or indirect. Based on this premise, this research aimed to analyze the professional performance evaluation policies of technical administrative civil servants at Federal University of Paraíba. It verified, through the perception of the managers responsible for the evaluation process, within the institution, and the servant’s perception of the servants themselves (called TAs), who offer services to the community; it also verified if this professional performance evaluation process has an impact on the improvement of the services provided by the institution. In order to do so, we sought to answer the following question: What are the impacts of the professional performance evaluation policies of civil servants (TA) at UFPB in the services offered by them, under the managerial perspective, responsible for the evaluation process, and under the perspective of servants (TAs) working at the Servant Service Department located in the Personnel management Office? The methodology was based on the phenomenological approach. The research was classified as qualitative, applied, exploratory and descriptive, with bibliographic, document and field research procedures. The semi-structured interview was used as the data collection method. The research subjects were the servants (TAs) working at the Servant Service Department located in the Personnel Management Office and the managers in charge with the professional performance evaluation process. For the data analysis, the Content Analysis (Bardin, 1977) was used. The results pointed that there is no impact concerning the servants’ professional performance in the services offered by them, however when the evaluation is carried out properly, the impacts are positively seen in the sectoral services in general